ANALYSIS OF THE OPTIMIZATION OF THE IMPLEMENTATION OF SERVICE MARKETING MIX ON STUDENT'S SATISFACTION - Basari, Moch. Aziz; Usmar, Dani; Kader, Mukhtar Abdul (Universitas Brawijaya, Indonesia, 2017)
This study aims to analyze how much influence the marketing mix to the satisfaction of Students of the Faculty of Economics, Galuh University of Ciamis. Marketing Mix Services by combining Price (X1), Place (X2), Process (X3), People (X4) and Physical Evidence (X5) in synergy to affect student satisfaction and analyze which of the five marketing mix that most influence on student satisfaction. Methods of data collection method used in this research Field Research (observation, interviews, and questionnaires) and using a Likert scale and the determination of the sample used was accidental sampling as many as 96 samples. With the method simple and multiple linear regression. The results are partially Price (X1): 15:46%, Place (X2): 18:36%, Process (X3): 39.22%, People (X4): 36.24% and Physical Evidence (X5): 61.82%, and simultaneously at 68.09%. 31.91% influence of other variables. By using SPSS shows of the five components of marketing mix variables only place (X2) and Physical Evidence (X5) positive and significant impact on student satisfaction (Y), because the level of significance of <0.05, while the variable price (X1), process (X3) and people (X4) effect on student satisfaction (Y), but not significant. Due to the significance level above 0.05 (> 005).